Generational leader transition: Millennial leader's leadership styles in multigenerational companies - Ismudarmawan, Nahdah Sabrina; Taufik Akbar Rizqi Yunanto (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
One of the service companies in Surabaya is currently undergoing a generational leadership transition, marked by the emergence of millennial leaders in key positions. This study aims to explore the leadership style of a millennial leader in a multigenerational team context, with a focus on identifying behaviors aligned with the four dimensions of transformational leadership: idealized influence, inspirational motivation, individualized consideration, and intellectual stimulation. Using a qualitative descriptive method, data were collected through participant observation over three working days and semi-structured interviews with the subject. The findings indicate that the subject actively applies transformational leadership, particularly through motivational encouragement, coaching, and inclusive decision-making processes. Although direct observation revealed stronger expressions of inspirational motivation and intellectual stimulation, interview data confirmed the presence of all four transformational dimensions in the subject’s leadership approach. This leadership style contributes to a positive team climate, increased engagement, creativity, and productivity. The study reinforces the relevance of transformational leadership in managing multigenerational teams and highlights the adaptive capacity of millennial leaders in contemporary organizational settings.